Analyzing the Musculoskeletal Flexibility in Young Females: The Impact of a Six-Week Surya Namaskar Intervention on Back Flexibility and Lumbar Flexion - Suchishrava Dubey; Prashant Kumar Choudhary (OVS LLC, 2024)
Objectives. This study aimed to investigate the effects of a structured six-week Surya Namaskar (Sun Salutation) regimen on back flexibility and lumbar flexion in female college students. Materials and methods. Thirty female college students from the Gwalior District participated in the study and were randomly assigned to either an experimental group (Surya Namaskar regimen) or a control group. Baseline measurements of age, height, weight, and initial flexibility were recorded. The experimental group engaged in a six-week Surya Namaskar program, while the control group maintained their regular activities. Back flexibility and lumbar flexion were assessed using standardized tests before and after the intervention period. Results. Statistical analysis revealed significant improvements in back flexibility and lumbar flexion in the experimental group following the six-week Surya Namaskar regimen. Specifically, the experimental group demonstrated a substantial increase in both back flexibility (mean change ± SD: 3.20 ± 0.95 cm) and lumbar flexion (mean change ± SD: 1.50 ± 0.75 cm), whereas the control group showed no significant changes in these parameters. Conclusion. The findings underscore the effectiveness of Surya Namaskar in enhancing musculoskeletal flexibility among female college students. Integrating Surya Namaskar into educational programs could potentially benefit physical health by improving back flexibility and lumbar flexion, thus supporting overall musculoskeletal health and reducing the risk of injuries. Further research could examine the long-term effects and mechanisms underlying these improvements across diverse populations.